Development of STEM-Based Electronic Student Worksheets in Aquatic Ecology Subjects to Improve Students Creative Thinking - Fauzi, M. Irsyad; Suwondo, Suwondo; Wulandari, Sri (Journal of Educational Sciences, 2024)
The 21st century is also known as the era of science and communication. To face the challenges of the 21st century, quality human resources are needed through the education sector. This research aims to: 1) determine the validity of STEM-based e-LKM in the Aquatic Ecology course, 2) determine the practicality of STEM-based e-LKM, and 3) determine the increase in students' creative thinking after using STEM-based e-LKM. e-LKM development is carried out using the ADDIE model at the analysis, design, development, implementation and evaluation stages. The research subjects are material experts, education experts, media experts and students. Expert validity data was collected using an expert validation questionnaire which was analyzed using the Pearson correlation test, data on creative thinking skills was measured by asking students questions. The research results show that the validity of e-LKM is in the very valid category of 3.76 from an average of 3 experts who are validators. And the student's post test score is in the very good category, namely 87.15. It can be concluded that this research produces e-LKM for aquatic ecology courses that are valid and practical.